Pengaruh Kemudahan Transaksi, Keamanan Transaksi, dan Kepercayaan terhadap Minat Penggunaan QRIS di Kabupaten Tasikmalaya - Wafa Nur Fitri; Aldy Agustian (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of transaction convenience, transaction security, and trust on the intention to use the Quick Response Code Indonesian Standard (QRIS) in Tasikmalaya Regency. This research employed a quantitative method with descriptive and verificative approaches. Primary data were collected through questionnaires distributed to 120 respondents selected using purposive sampling. Data were analyzed using SPSS version 25 through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results indicate that all research instruments are valid and reliable. Transaction convenience has a positive and significant effect on the intention to use QRIS. Transaction security also has a positive and significant effect on the intention to use QRIS. Trust has a positive and significant effect and is the most influential variable among the three independent variables. Simultaneously, transaction convenience, transaction security, and trust significantly affect the intention to use QRIS. The coefficient of determination shows that these variables explain 66.3% of the variation in QRIS usage intention, while the remaining 33.7% is influenced by other factors. These findings suggest that improving convenience, security, and trust can increase public interest in using QRIS.